The impacts of tsunami on the well-being of the affected community in Kuala Muda, Kedah, Malaysia - Asmawi, M. Zainora; Ibrahim, Aisyah Nadhrah (IACSIT Press, 2013)
The tsunami of 26 December 2004 was one of the most devastating tragedy ever occurred to men in the history of human civilization. Approximately 250,000 lives perished, millions injured and suffered, while the destruction of property loss of opportunities cannot be accurately estimated. The impact of the tsunami on environmental destruction shows that damage was inflicted on natural resources such as coral reefs, mangroves, sand dunes and other coastal ecosystem that acted as wave defense barriers. Moreover, inlands, wetlands and agricultural land were salinated and natural resources for livelihood and for source of income were badly affected, especially for coastal communities who were involve in fisheries. The situation worsened as basic facilities were also destroyed. As such, this research focuses on assessing and identifying on how the impacts of the tsunami on the infrastructure and environmental resources affected the community well-being inKuala Muda, Kedah, Malaysia. This study focuses on the impacts of tsunami on the affected community well-being in the coastal zone on the basis of available primary and secondary sources. Primary sources included questionnaires, interviews and observations while the secondary resources included books,government and international reports, scientific journals, maps and articles that highlighted tsunami related issues. The study tries to seek for both qualitative and quantitative impacts and also tries to find out some solutions that would help to minimize the impact of the tsunami on the community well-being. The information gained from this study can be used to help the community as well as the agencies involve in order to minimize the impacts of the tsunami on the community and develop a more effective mitigation measures for other environmental disasters such as tsunami. Besides, the research may help to create awareness on the community to be prepared in facing disastrous situation such as the tsunami. Through community preparedness, the impact can be minimized and reduced. As for the authority, this research may be of great assistance by allowing them to make better decision.